FROM TEXTBOOK TO TERRA: TRANSFORMING POETRY EDUCATION WITH ENVIRONMENTAL THEMES AND LECTORA INSPIRE - Umaya Sari Daulay; Khairil Ansari; Mara Untung Ritonga (LLDIKTI Wilayah X, 2024)
This research aims to develop teaching materials and improve students' poetry writing abilities, and determine the suitability of teaching materials that have been developed according to expert judgment and students at SMAS Jenderal Sudirman. This research method uses Research and Development (R & D) which begins with a preliminary study followed by the product development and assessment stages. The research subjects were determined using a purposive sampling technique consisting of 35 students. Data were collected using interviews and questionnaires in the form of questionnaires. The procedure for this research is the process of preparing teaching materials to improve the ability to write poetry on environmental themes through the following stages: (a) Preliminary study, by conducting interviews and questionnaires with teachers and students. (b) Syllabus analysis study and analyzing basic competencies in preparing teaching materials (c) Preparing teaching materials with the help of Lectora Inspire (d) Trial trials (e) Data processing and evaluation. The conclusion of this research is the development of teaching materials for writing poetry with an environmental theme with the help of Lectora Inspire, namely materials developed from the 2013 curriculum and subject syllabus. Its effectiveness on students produced several averages, the first of which was tested individually, namely 77.08% which was classified as